Economics of cultivation of Melia dubia- Hybrid Napier silvi-pasture models - Thakur, Narender Singh; Prajapati, D R; Singh, Narendra; Gunaga, R P; Bhuva, D C; Mevada, R J (Indian Journal of Agroforestry, 2022)
The present investigation was undertaken over two years to assess the economic feasibility of M. dubia (2×2, 3×2, 3×3, 4×2, 4×4 m)-hybrid napier (HN) silvi-pasture and sole HN cropping systems. On account of hybrid napier fresh forage production, highest net returns to the tune of Rs. 262170 ha-1year-1, were fetched from M. dubia (2 x 2 m)-HN. Whereas, on account of M. dubia wood biomass (at 5 years of age) maximum net returns to the tune of Rs. 455664 ha-1 were obtained from M. dubia (3 x 2 m)-HN. M. dubia (3 x 2 m)-HN system provided highest total net returns of Rs. 947964 ha-1, followed by M. dubia (4 x 2 m)-HN system and M. dubia (3 x 3 m)-HN with total net returns of Rs. 877559 and Rs. 848486 ha-1, respectively. Economic feasibility analysis revealed that the highest BCR (6.62), NPV (Rs. 627902), IRR (5.62%) and shortest PBP (0.17 year) was realized from M. dubia (3 x 2 m)-HN system. Overall, on the basis of total net returns the land use systems follow the order: M. dubia (3 x 2 m)-HN>M. dubia (4 x 2 m)-HN>M. dubia (3 x 3 m)-HN>M. dubia (2 x 2 m)-HN>M. dubia (4 x 4 m)-HN>Sole HN. Whereas, on the basis of BCR the top three land use systems came out are M. dubia (3 x 2 m)-HN>M. dubia (4 x 2 m)-HN>M. dubia (3 x 3 m)-HN>.